Challenges Encountered by Midwives When Providing Care to Preterm Babies at Selected Hospitals in Mopani District of Limpopo Province, South Africa - Mahwasane, Thendo (My University, 2018)
Introduction: During the provision of care to preterm babies, midwives encounter many problems and challenges which may vary according to the gestational age of the women, condition of the foetus, availability of equipment and resources, and experience of the midwives. In addition, poor working conditions, feelings of insecurity, staff shortage, and lack of support from the management and having to deal with parents who do not comply with the hospital management plan for their babies; all contribute to the problems faced by midwives. The purpose of this study was to determine challenges encountered by midwives when providing care to preterm neonates at selected hospitals in the Mopani District of Limpopo Province, South Africa. Methods: Qualitative research in this study was conducted in a natural setting at the selected hospitals. The target population was the midwives who have been working in maternity wards for at least two years and were on duty during the period of data collection. Non-random purposive sampling was used to select the participants. Data were collected using unstructured interviews, which were tape recorded and transcribed. The six steps as described by Creswell were used for data analysis. Trustworthiness was ensured by using the model of Lincoln & Guba that included credibility, dependability, confirmability and transferability. Ethical principles, namely, permission to conduct the study, informed consent from participants, privacy, confidentiality, autonomy, anonymity and respect were observed. Results: When midwives provide care to preterm babies they often encounter multiple challenges which can be human or material resource related. In his study, midwives were found to perform their duties in the face of multiple challenges, including staff vi shortages, which resulted in exhaustion of the available midwives. Nursing a preterm baby is a challenge on its own as these babies are likely to develop clinical problems related to immaturity, e.g., hypoglycaemia, hypothermia, jaundice, sepsis and respiratory distress. Mothers may be traumatised and find it difficult to accept their babies as they are, this leads to lack of cooperation in the care of the neonate and it becomes a problem for the midwives who are directly providing such care. The aforementioned challenges are related to all the four major concepts of human caring as described by Jean Watson which are health, human being, nursing and environment. Recommendations: It is recommended that further research be conducted on the same topic, but in a different setting to generate more knowledge. Policy makers should work together with health care professionals who are directly involved in the care of preterm babies to improve the practice of the contents in the policies.
MCur
Department of Advanced Nursing Science
Keywords: Challenges encountered; UCTD; Midwives; Preterm babies; Preterm birth; Provision of care